Introducing Upfront Money Can Decrease Discounting in Intertemporal Choices with Losses - Jiang, Cheng-Ming; Sun, Hong-Yue; Zheng, Sheng-Hua; Wang, Liang-Jun; Qin, Yu (Frontiers in Psychology, 2016)
People generally tend to advance gains and postpone losses in intertemporal choice. Jiang et al. (2014) recently showed that adding upfront losses or gains to both smaller and sooner (SS) and larger and later (LL) rewards can decrease people’s discounting. To account for this decrease, they proposed the salience hypothesis, which states that introducing upfront losses or gains makes the money dimension more salient than not, thus increasing people’s preference for LL rewards. Considering that decreasing the discounting of delayed losses is imperative and that most previous studies have focused on intertemporal choices with gains, in the current paper we conducted two experiments and used hypothetical money outcomes to examine whether the effect of upfront money could be extended to intertemporal choices with losses. The results showed that when both SS and LL intertemporal losses were combined with an upfront loss or gain, people’s discounting rate decreased and the preference for the SS option increased. This finding further supports the salience account.